SARS-CoV-2 Genome Analysis of Pediatric Patients in Konya Region, Turkey - Tasbent, Fatma Esenkaya; Özdemir, Mehmet; Akcan, Özge M.; Kurt, Esma K. (Journal of Pediatric Infectious Diseases, 2021)
Objective Genome sequencing is useful for following the change in mutation and variants in viral agent during pandemics. In this study, we performed next-generation sequencing of severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) complete genomes on pediatric patients.Methods Six pediatric patients aged 0 to 18 years who were positive for SARS-CoV-2 by reverse transcription polymerase chain reaction were included in this study. SARS-CoV-2 genome sequencing was performed using Oxford Nanopore Technologies MinION, following the ARTIC Network protocols. Sequencing data were obtained using the FASTQ program and quality assessment was evaluated. The sequence information of all samples was uploaded to the Global Initiative on Sharing All Influenza Data (GISAID) database. Genome, variant, clade, and phylogenetic tree analyses were performed with bioinformatic analysis.Results Two of these six samples were at 20A, two were at 20B, and two were at 19A in the nextstrain clade. According to Pango lineages, B.1.36, B.1.218, B.1, and B.1.260 lineages were detected. A total of 84 mutations were observed in all samples. None of the variants were classified as variants of concern (VOC) nor variants of interest (VOI) according to the Pango database.Conclusion This study is the first comprehensively sequence analysis registered in the GISAID database reported from the Konya region in Turkey. Similar studies will be informative to track changes in the virus genome, obtain epidemiological data, guide studies on diagnosis and treatment, and evaluate vaccine efficacy.
Keywords: COVID-19; SARS CoV-2; variation; genome sequencing; clade